1988
DOI: 10.1002/mrd.1120210309
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage characteristics of mouse embryos inseminated and cultured after zona pellucida drilling

Abstract: The effects of zona drilling on mouse embryo development in vitro were evaluated. Following insemination, sperm were immediately concentrated at the area of drilling, and in zona-drilled eggs, pronuclei appeared 30-50 min earlier than in zona-intact controls. Zona-drilled oocytes fertilized at significantly higher rates than undrilled controls and, consequently, a greater percentage of eggs inseminated after zona drilling reached the blastocyst stage. The attrition rates of zona-drilled embryos at each cleavag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 16 publications
1
26
0
1
Order By: Relevance
“…It has been proposed that an artificial breach in the zona by ICSI or AH and subsequent herniation of blastomeres through the hole in the zona during blastocyst expansion might result in mechanical splitting of the blastocyst and formation of MZ twins (Talansky & Gordon 1988). This phenomenon has been recorded by time-lapse photography in bovine embryos (Van Langendonckt et al 2000).…”
Section: Zona Pellucida Manipulationmentioning
confidence: 99%
“…It has been proposed that an artificial breach in the zona by ICSI or AH and subsequent herniation of blastomeres through the hole in the zona during blastocyst expansion might result in mechanical splitting of the blastocyst and formation of MZ twins (Talansky & Gordon 1988). This phenomenon has been recorded by time-lapse photography in bovine embryos (Van Langendonckt et al 2000).…”
Section: Zona Pellucida Manipulationmentioning
confidence: 99%
“…It is done in ICSI, assisted hatching (AH) and blastomere biopsy for preimplantation genetic diagnosis (PGD). It is argued that artificial rupture of the zona pellucida in these procedures results in the presence of an orifice with subsequent herniation of the blastomeres, and blastocyst expansion may result in a mechanical unfolding of the embryo, resulting in MZT (Talansky & Gordon, 1988;Van Langendonckt et al, 2000). Saito et al (2000) reported 9 MZT from a total of 279 pregnancies (3.2%), with an increased risk in cases where manipulation originated wider rupture of the zona pellucida.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies have documented an increased risk for MZ twinning in ART pregnancies that included assisted hatching (Hershlag et al 1999;Schieve et al 2000), and animal studies have shown that MZ twinning can be induced through mechanical or chemical manipulation of the zona pellucida (Allen and Pashen 1984;Picard et al 1985;Sotomaru et al 1998;Talansky and Gordon 1988).…”
Section: Assisted Reproductive Technologiesmentioning
confidence: 99%